2018
DOI: 10.1101/310896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inter-annual variation in seasonal dengue epidemics driven by multiple interacting factors in Guangzhou, China

Abstract: Vector-borne diseases display wide inter-annual variation in seasonal epidemic size due to their complex dependence on temporally variable environmental conditions and other factors. In 2014, Guangzhou, China experienced its worst dengue epidemic on record, with incidence exceeding the historical average by two orders of magnitude. To disentangle contributions from multiple factors to inter-annual variation in epidemic size, we fitted a semi-mechanistic model to time series data from 2005-2015 and performed a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 62 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…These values were selected as previous studies demonstrated that the optimal lags of meteorological variables used for dengue forecasting are usually not larger than 12 weeks [ 49 54 ]. In addition, the ordinal number of the forecast week (1–52 for the year of 2015, 2016, 2017, and 2018 and 1–53 for 2014) as well as year (2014–2018) were treated as two predictor variables to account for seasonality and long-term changing trend of dengue occurrence [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…These values were selected as previous studies demonstrated that the optimal lags of meteorological variables used for dengue forecasting are usually not larger than 12 weeks [ 49 54 ]. In addition, the ordinal number of the forecast week (1–52 for the year of 2015, 2016, 2017, and 2018 and 1–53 for 2014) as well as year (2014–2018) were treated as two predictor variables to account for seasonality and long-term changing trend of dengue occurrence [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reveal that the dengue outbreaks are characterised by seasonal and multi-annual pattern of occurrence [ 8 ]. Studies undertaken in several parts of the world provide evidence that the periodic outbreaks of dengue are closely associated with local weather conditions and climate cycle of El Niño Southern Oscillation (ENSO) [ 9 11 ], but the risk of outbreaks differ based on the strength of ENSO [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue virus (DENV) transmission is influenced by multiple overlapping drivers, including human and mosquito movement; climate and environmental factors that affect mosquito abundance, contact with human hosts, and vector-virus interactions; human host immunity; and virus genotype (21)(22)(23)(24)(25)(26). Hence, predicting the epidemiological impact of drastic changes in human mobility on DENV transmission is difficult because of the large number of potentially influential variables that interact in complex ways.…”
Section: Introductionmentioning
confidence: 99%